2021
DOI: 10.1186/s12929-020-00705-3
|View full text |Cite
|
Sign up to set email alerts
|

FKBP10 promotes proliferation of glioma cells via activating AKT-CREB-PCNA axis

Abstract: Background Although the availability of therapeutic options including temozolomide, radiotherapy and some target agents following neurosurgery, the prognosis of glioma patients remains poor. Thus, there is an urgent need to explore possible targets for clinical treatment of this disease. Methods Tissue microarrays and immunohistochemistry were used to detect FKBP10, Hsp47, p-AKT (Ser473), p-CREB (Ser133) and PCNA expression in glioma tissues and x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
(21 reference statements)
1
21
0
Order By: Relevance
“…To assess whether the remission of psoriatic lesions after TDG treatment may be due to the prevention of the over-proliferation of KCs, we verified the Ki67 and PCNA-positive cells in each group. Ki67 and PCNA are classical markers of cell proliferation in a variety of diseases ( Alhosaini et al, 2021 ; Cai et al, 2021 ). As expected, following TDG treatment, the number of Ki67 and PCNA-positive cells in IMQ-induced psoriasis-like mice decreased significantly ( Figure 2 ; Supplementary Figure S1 ), which is consistent with the results of previous studies ( Ru et al, 2020 ; Thatikonda et al, 2020 ; Tomalin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether the remission of psoriatic lesions after TDG treatment may be due to the prevention of the over-proliferation of KCs, we verified the Ki67 and PCNA-positive cells in each group. Ki67 and PCNA are classical markers of cell proliferation in a variety of diseases ( Alhosaini et al, 2021 ; Cai et al, 2021 ). As expected, following TDG treatment, the number of Ki67 and PCNA-positive cells in IMQ-induced psoriasis-like mice decreased significantly ( Figure 2 ; Supplementary Figure S1 ), which is consistent with the results of previous studies ( Ru et al, 2020 ; Thatikonda et al, 2020 ; Tomalin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that SERPINA3 promotes the proliferation of melanoma and human liver cancer cells 20,21 . In the present study, the relationship between SERPINA3 and other previously verified proliferation‐related molecules, including MCM6, 16 IGFBP2 , 15 and FKBP10 18 was evaluated. A strong correlation between the expression of SERPINA3 and these molecules in glioma suggests that SERPINA3 may participate in the proliferation of glioma cells.…”
Section: Discussionmentioning
confidence: 80%
“…For the same cases, we previously reported high expression of IDH1 mutation, 17 MCM6 protein, 16 FKBP10 protein, 18 and IGFBP2 mRNA 15 . Here, we simultaneously analyzed the relationship between SERPINA3 expression and the alterations biomarkers.…”
Section: Resultsmentioning
confidence: 89%
“…A prognostic role has also been reported for some of these genes, both negative ( ERRFI1 ) [ 25 ], and positive ( SLC44A3 ) [ 29 ]. Additionally, several of the differentially expressed genes are proposed to be potential therapeutic targets, such as FAIM2 in small cell lung carcinoma [ 18 ], ERRFI1 in pancreatic carcinoma [ 25 ], RASA4 in triple-negative breast carcinoma [ 53 ], FKBP10 in gliomas [ 7 , 18 ], metastatic gastric carcinoma [ 16 ] and lung carcinoma [ 38 ], and CACNA2D in prostate carcinoma [ 18 ]. Overview of the most interesting genes differentially expressed between the cell-lineage based groups of PitNETs has been presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%